Awareness and reported violations of the WHO International Code and Pakistan's national breastfeeding legislation; a descriptive cross-sectional survey - Faragher Brian; Kiani Ayyaz; Salasibew Mihretab; Garner Paul (BMC, 2008)
Abstract Background National legislation in Pakistan adopted the International Code of Marketing of Breastmilk Substitutes in 2002 to restrict the promotion of infant formula feeding. Our objectives were to assess health professionals' awareness of this law in urban government hospitals and describe their reports of violations, including receiving free samples, gifts and sponsorship. Methods Structured interviews were conducted with health staff between July and August 2006 at 12 urban government hospitals in Islamabad, Rawalpindi and Peshawar including paediatricians, obstetricians, nurses, resident doctors, midwives and lady health visitors (LHVs). Results Of the 427 health workers interviewed, the majority were not aware of the national breastfeeding law (70.5%; n = 301) or the International Code (79.6%; n = 340). Paediatricians, and staff who had been working for 10 years or more, were more likely to be aware of the law [OR = 7.00, 95% CI 3.12, 15.7 (paediatricians); OR = 2.48, 95% CI 1.45, 4.24 (10 years working)]. More than one third (38.4%, n = 164) had received small gifts such as pens, pencils and calendars; 12.4% (n = 53) had received sponsorship for training or conferences; and 15.9% (n = 68) had received free samples of infant formula from the Companies. Staff who were aware of the law were also more likely to report receiving gifts (OR = 1.64, 95% CI 1.08, 2.51) and free samples (OR = 1.86, 95% CI 1.09, 3.19). Conclusion Most hospital health professionals were unaware of national breastfeeding legislation in Pakistan, and infant formula companies were continuing to flout the ban on gifts, free samples and sponsorship for health staff.